Development of comparative genomic hybridization(CGH) technique for the study of nasopharyngeal carcinoma(NPC) - Alwi, Zilfalil; Khan, Ali; Jaafar, Hasnan; Yusof, Narazah Mohd; Ashman, James; Idris, Fauziah Mohd (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2009)
NPC is a disease in which malignant cells are formed in the tissue of nasopharynx. It is a highly prevalent disease in Southern China and Southeast Asia including Malaysia. CGH is a molecular cytogenetic technique which is used to identify imbalanced genetic alterations in this malignancy. Twenty eight samples were obtained. Out of this; twelve tumors were extracted from twelve NPC biopsies while twelve references DNA was extracted from twelve normal controls peripheral blood. Tumor DNA and normal DNA was labeled by nick translation method with green and red fluorescent dyes. These were hybridized at metaphase chromosomes DNA and counterstained with DAPL Finally, the image was captured and analyzed. Chromosomal gains that were found in this study were 4q26, llql3-ql4, 9pl3, 8ql3-q22 and 10q22- q26 while chromosomal losses were found at region 20p12 and 13q21-q31. We believe this study has provided the platform for further investigations to locate possible tumorsuppressor genes and oncogenes in our NPC patients.